Genetic Diversity Evaluation of Moringa oleifera, Lam from East Flores Regency Using Marker Random Amplified Polymorphic DNA (RAPD) and Its Relationship to Chemical Composition and In Vitro Gas Production - Markus Miten Kleden; Hendrawan Soetanto; Kusmartono Kusmartono; Kuswanto Kuswanto (AGRIVITA, Journal of Agricultural Science, 2017)
The research objective was to evaluate the genetic diversity of Moringa oleifera, Lam (MO) and its relationship to chemical composition and in vitro gas production (IVGP). Fresh MO leaves were kept frozen in ice gels pack until laboratory analysis. Four methods applied: RAPD marker for measuring DNA concentration and purification; Kjeldhal and HPLC for analysing proximate and amino acid (AA) composition; and IVGP. MO’s four distinct morphology found: green, red, reddish green and aromatic green. RAPD result analysis was 68.8-74.7 %, it means those MO had a close genetic similarity. The morphological differences are also related to leaves chemical composition variation. The highest protein and AAs content were found in aromatic green MO. Total IVGP at 96 hours reached 95.9, 99.3, 111, 115 mL per 500 mg DM in aromatic green, green, reddish green, red MO, respectively and statistically among those was highly significant difference (P<0.01). However, DM and OM digestibility did not differ significantly and estimated ME contents were similar suggesting MO leaves had sufficient fermentable nitrogen amount required to ensure rumen microbes normal activities. Conclusively, those MO has a close genetic relationship but the aromatic green MO more beneficial due its higher content of crude protein and AAs.